Influence of traps reversibility on hydrogen permeation and retention in Eurofer97. (1st August 2022) - Montupet-Leblond, F.; Hodille, E.A.; Payet, M.; Delaporte-Mathurin, R.; Bernard, E.; Charles, Y.; Mougenot, J.; Vartanian, S.; Grisolia, C.
Abstract: The presence of three trapping sites in Eurofer97 and the diffusion and trapping parameters obtained in a previousarticle are confirmed using an additional thermal desorption spectrometry experiment. Using these parameters, permeation cycles are simulated using the diffusion–reaction code mhims in order to study the influence of each trapping site on the permeation dynamics. The concept of traps reversibility is used to qualify this influence. The analysis indicates that the reversibility of the trapping sites is a key parameter in diffusion and permeation dynamics, which must be accounted for to get accurate predictions of hydrogen inventory and permeation.